Creep-fatigue life evaluation of high chromium ferritic steel under non-proportional loading (Fracture and Structural Integrity, 2016)
T Multiaxial creep-fatigue tests under non-proportional loading conditions with various strain rates were carried out using a hollow cylinder specimen of a high chromium ferritic steel at 823K in air to discuss the influence of non-proportional loading on failure life. Strain paths employed were a push-pull loading and a circle loading. The push-pull loading test is proportional strain path test. The circle loading test is non-proportional strain path test in which sinusoidal waveforms of axial and shear strains have 90 degree phase difference. The failure life is affected largely by the strain rate and the non-proportional loading. This paper presents a modified strain range for life evaluation considering the strain rate based on a non-proportional strain parameter proposed by authors. The strain range is a suitable parameter for life evaluation of tested material under non-proportional loading at high temperature.
Keywords: Life evaluation; Creep-fatigue; Multiaxial strain; Nonproportional loading; High chromium ferritic steel